(untitled) - The World Bank (WB) in the Asia and Pacific Region; Human Development Department (Ha Noi, 2009)
The report focuses on the higher education system, including public, semi-public and non-public institutions, in connection to the labor market in Vietnam. Many questions are addressed in the report, such as whether Vietnam should significantly expand the scope of the higher education system, whether this system provides relevant skills for employment, the promotion of productivity and innovation and how it can be improved, and what incentive mechanisms are need for better relevance of the system to the demands of the labor market.
Keywords: Education, Higher,Higher education and state,Giáo dục đại học và quốc gia,Giáo dục, Đại học; Vietnam,Vietnam,Việt Nam,Việt Nam